ILC2s in Virus-induced Asthma Exacerbations: A Starring or Supportive Role? - Hershenson, Marc B. (American journal of respiratory and critical care medicine, 2021)
Hershenson discusses the study by Dhariwal and colleagues on the role of ILC2s in virus-induced asthma exacerbations, which is published within the issue. The team measured nasal and BAL cytokines and ILC2s in control subjects and subjects with asthma before and after nasal challenge with rhinovirus A16 (7). Patients with asthma were required to have a doctor diagnosis, treatment with inhaled corticosteroids, airways hyperresponsiveness by bronchoconstrictor challenge testing, and evidence of atopy on skin prick testing. ILC populations were identified by flow cytometry. The results establish ILC2s as a likely mediator of viral-induced exacerbations in patients with allergic asthma.